Influence of air velocity on self-paced exercise performance in hot conditions - Bright, F. M.; Clark, B.; Jay, O.; Périard, J. D. (Medicine & Science in Sports & Exercise, 2023)
Purpose This study aimed to determine the effect of different air velocities on heat exchange and performance during prolonged self-paced exercise in the heat.